RANCANG BANGUN ALAT CETAK PLASTIK VAKUM UNTUK MENURUNKAN PROSENTASE CACAT PRODUK DI LABORATORIUM METROLOGI DAN CETAK PLASTIK - Nailul Ulum, Muhammad Showi; Harmanto, Sri; Satito, Aryo; Yanuar, Padang; Hamid, Abdul; Iyadul, Fatih (Journal of Mechanical Engineering and Applied Technology, 2024)
AbstrakVacum Forming is process packaging in industrial, wich one deformation of plastic and formed on mold with difference preassure. In food and drinking industrial show positive progress and make bigger contribution for economic grow in Indonesia. At this moment Vacum Forming industrial in Indonesia is just owned big industrial wich have good purchasing power tools in range hundreds of million to billions of rupiah. Metrologi dan Cetak Plastik laboratory in Teknik Mesin Politeknik Negeri Semarang one of the topics is Vacum Forming. Equipment Used is very simple, manny time try and erors needed for have good product without any defects by way temperature varible, pressure, warm-up time and forging. The most difficult is warm-up process where must tu set the hight temperature waring and gap between the material and the heater. The purpose of the research is to know the influence of warming temperatures, time of warming, thick of plastic and pressure on the quality, The result of this research the best variable is time for warm-up 135 second, time of forging 40 second. Ticknes variable is 0,5 mm, 0,3 mm and 0,25mm, the best ticknes of plastic is 0,25 mm.